Management and prevention of varicella and measles infections in pediatric solid organ transplant candidates and recipients: an IPTA survey of current practice - Pittet, Laure; Danziger-Isakov, Lara; Allen, Upton D.; Ardura, Monica I.; Chaudhuri, Abanti; Goddard, Elizabeth; Höcker, Britta; Michaels, Marian G.; Van der Linden, Dimitri; Green, Michael; Posfay-Barbe, Klara M. (Pediatric transplantation, 2020)
Background Varicella and measles infections can be life-threatening after solid organ transplantation (SOT) but may be preventable with live-attenuated vaccines (LAV). Methods This survey conducted in January 2019 among subscribers of the International Pediatric Transplantation Association listserv aimed to explore the current strategies to prevent and manage both infections in the pediatric SOT population, including recommending LAV after SOT. Results The answers given by 95 pediatric SOT healthcare workers show that these strategies are not yet optimal and call for further education. In particular, 59% of respondents are unnecessarily waiting for a SOT candidate to be >1 year of age to start administrating LAV before SOT. Interestingly, most respondents are willing to administer LAV after SOT (57%), and a fifth (21%) are already doing so, off-label. The survey queried the precautions taken to improve safety evaluations after LAV, and identified knowledge gaps and practitioners’ concerns. Conclusion The results of this survey could be used as a starting point for education and promotion of the safe administration of LAV in carefully selected SOT recipients; in turn, this would increase available data that would contribute to the development of evidence-based guidelines by the transplant societies and ultimately prevent these infections after SOT.